The physiological and perceived effects of drafting on a group of highly trained distance runners - Corvalan-Grossling, V. (1995)
Abstract: This investigation examined and compared submaximal oxygen consumption, carbon dioxide production, minute ventilation, and heart rate responses during indoor track running in three running configurations in a group of highly trained distance runners. Maximal oxygen consumption performance testing was conducted to determine at what percentage of their maximal aerobic capacity the subjects were performing at during the test trials. Oxygen consumption, carbon dioxide production, minute ventilation, and heart rate values were measured every 20 seconds during all test trials using a portable calorimeter. Following each trial, runners were asked to rate their perceived exertion using the Borg scale. Subjects were randomly assigned configurations and order of testing. A recovery period of 15 minutes was required between all trials. Nine subjects were tested at 4.47 m/s in three positions, L, Dl and D2. During the 4.47 m/s trials, drafting (D1 + D2) significantly reduced oxygen consumption (4.02+/-0.18 l/min leading versus 3.81+/-0.13 l/min drafting), and carbon dioxide production (3.74+/-0.23 l/min leading versus 3.32+/-0.13 l/min drafting) (p<0.05). There was no significant difference in the reduction of oxygen consumption or carbon dioxide production between running directly behind a single runner, position D1, and running behind on the inside of a triangle, position D2. Minute ventilation and heart rate were not significantly reduced during the drafting (D1+D2) trials. There was a significant reduction in the rating of perceived exertion for running behind on the inside of a triangle, position D2. A sub-group of five subjects was also tested at 5.36 m/s in two positions, L and D1. During the 5.36 m/s trials, drafting in position D1 had the same effect as it did at the 4.47 m/s with the exception that the reductions were slightly larger than those observed for the slower pace. Drafting in position Dl substantially reduced oxygen consumption (4.76+/-0.20 l/min leading versus 4.35+/-0.20 l/min D1), and carbon dioxide production (4.44+/-0.28 l/m in leading versus 4.16+/-0.26 L/min D1). Minute ventilation, heart rate, and rating of perceived exertion were not reduced during the drafting (D1) trials. These results demonstrate that running within the aerodynamic shadow of another runner is very advantageous for distance runners. Both drafting positions tested were found to be equally effective in conserving energy. Drafting on the inside of a triangle was the position of choice. Coaches should expose athletes to drafting situations in training so that athletes can successfully employ this energy-saving strategy. One must also be aware that athletes who consistently run within a pack or drafting are not obtaining the full benefits of their training regimen. (Corvalan-Grossling, V. The physiological and perceived effects of drafting on a group of highly trained distance runners, 1995. M.S., University of British Columbia. (113pp 2f $10.00) PE 3587)